2018
DOI: 10.3892/mco.2018.1677
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal effect following radiation monotherapy in breast cancer: A case report

Abstract: Radiotherapy has been found to be valuable for the control and eradication of local foci in various malignant tumors. The abscopal effect is determined as a systemic antitumor response at a distance from the irradiation site invoked by local irradiation. We herein present an extremely rare case of breast cancer in a 64-year-old woman, in whom the abscopal effect was observed after radiotherapy induced an antitumor response in all metastatic lesions, without any combination therapy. The patient was admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
(16 reference statements)
1
34
0
Order By: Relevance
“…Our hypothesis to explain the sustained disease remission post virus administration in this patient, and the fact that neither of her focal recurrences were followed by systemic disease relapse, was that the virotherapy had boosted her antitumor T-cell response and that this response was further boosted after each of the local radiotherapy treatments due Table 1 Positive T-cell responses against tumor-associated antigens before measles virotherapy. to the abscopal effect of radiotherapy, which has been well described in other malignancies [18][19][20]. Interestingly, analysis of T-cell responses in this patient showed high basal response to multiple TAA, which were sustained at all time points post virus administration, even years post virotherapy.…”
Section: Mv-nis Therapy Increased Taa-associated T-cell Responsessupporting
confidence: 60%
“…Our hypothesis to explain the sustained disease remission post virus administration in this patient, and the fact that neither of her focal recurrences were followed by systemic disease relapse, was that the virotherapy had boosted her antitumor T-cell response and that this response was further boosted after each of the local radiotherapy treatments due Table 1 Positive T-cell responses against tumor-associated antigens before measles virotherapy. to the abscopal effect of radiotherapy, which has been well described in other malignancies [18][19][20]. Interestingly, analysis of T-cell responses in this patient showed high basal response to multiple TAA, which were sustained at all time points post virus administration, even years post virotherapy.…”
Section: Mv-nis Therapy Increased Taa-associated T-cell Responsessupporting
confidence: 60%
“…The results raise the possibility that this effect could be induced in some human tumors. In fact, we have observed several instances in the clinic where partial irradiation of the tumor both combined with immune checkpoint blockade or alone have resulted in complete responses in the tumor despite limited dose to parts of the tumor (38,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the immunomodulatory effects of local therapy; radiotherapy promotes the immunological system by inducing immunogenic cell death and subsequently increasing the sensitivity of lymphocytes to tumor cells [37,[47][48][49][50]. Studies also have demonstrated that the abscopal effect of local treatment combined with immunotherapy enhances the efficacy of treatment for breast cancer cases in animal models [51].…”
Section: Discussionmentioning
confidence: 96%